Book Review: Books on Screens: Players in the Swedish e-book market - Hillesund, Terje (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2018)
Books on Screens: Players in the Swedish e-Book markets, by Annika Bergström, Lars Höglund, Elena Maceviciute, Skans Kersi Nilsson, Birgitta Wallin, & Thomas D. Wilson (eds.), Nordicom (2017), 238 pages.